2021
DOI: 10.1186/s12967-021-03114-8
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ-ERBB2 promotes HER2-positive breast cancer progression and metastasis via sponging miR-136-5p and miR-198

Abstract: Background Circular RNAs (circRNAs) are pivotal regulators of various human cancers and circ-ERBB2 is abnormally expressed in breast cancer cells. However, the role and mechanism of circ-ERBB2 in HER2-positive breast cancer are still unknown. Methods The circ-ERBB2 expressions in the tumor tissues of HER2-positive breast cancer patients were tested using quantitative real-time PCR. The circ-ERBB2 function was investigated by cell counting kit 8 ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Radioimmunoprecipitation assay buffer (Beyotime, Shanghai, China) was performed for extracting total proteins from cells, and then, 50 μ g proteins were used for protein analysis as previously depicted [ 16 ]. The incubation of primary antibody was at 4°C overnight and secondary antibody (Abcam, Cambridge, MA, USA; ab205718, 1 : 5000) was at 25°C for 1 h. The primary antibodies were shown as follows: anti-proliferating cell nuclear antigen (anti-PCNA; Abcam, ab92552, 1 : 1000), anti-Bcl-2 associated X (anti-Bax; ab53154, 1 : 1000), anti-YAP1 (Abcam, ab52771, 1 : 1000), anti-P65 (Abcam, ab16502, 1 : 1000), anti-phospho-P65 (anti-p-P65; Abcam, ab86299, 1 : 1000), anti-inhibitor of nuclear factor- κ B (anti-I κ B α ; CST, Boston, MA, USA, #4812, 1 : 1000), anti-phospho-I κ B α (anti-p-I κ B α ; CST, #2859, 1 : 1000), and anti-GAPDH (Abcam, ab9485, 1 : 3000).…”
Section: Methodsmentioning
confidence: 99%
“…Radioimmunoprecipitation assay buffer (Beyotime, Shanghai, China) was performed for extracting total proteins from cells, and then, 50 μ g proteins were used for protein analysis as previously depicted [ 16 ]. The incubation of primary antibody was at 4°C overnight and secondary antibody (Abcam, Cambridge, MA, USA; ab205718, 1 : 5000) was at 25°C for 1 h. The primary antibodies were shown as follows: anti-proliferating cell nuclear antigen (anti-PCNA; Abcam, ab92552, 1 : 1000), anti-Bcl-2 associated X (anti-Bax; ab53154, 1 : 1000), anti-YAP1 (Abcam, ab52771, 1 : 1000), anti-P65 (Abcam, ab16502, 1 : 1000), anti-phospho-P65 (anti-p-P65; Abcam, ab86299, 1 : 1000), anti-inhibitor of nuclear factor- κ B (anti-I κ B α ; CST, Boston, MA, USA, #4812, 1 : 1000), anti-phospho-I κ B α (anti-p-I κ B α ; CST, #2859, 1 : 1000), and anti-GAPDH (Abcam, ab9485, 1 : 3000).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research reported that circRNA is involved in many biological processes through multiple mechanisms [13]. CircRNA could influence cancer cell differentiation, proliferation, migration, protein cracking, and apoptosis based on the function of ceRNA or miRNA "sponge" [14][15][16]. These properties of circRNA allow it to become an ideal tumor biomarker for the diagnosis and therapy of BC cancer.…”
Section: Discussionmentioning
confidence: 99%
“…50 μg proteins were used for protein detection by western blot, as previously stated [17]. Radioimmunoprecipitation assay buffer (Sigma) was used for obtaining total proteins, and BCA Protein Assay Kit (Sigma) was exploited to determine protein concentrations.…”
Section: Methodsmentioning
confidence: 99%